2020
DOI: 10.1016/j.immuni.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Sequencing of Peripheral Mononuclear Cells Reveals Distinct Immune Response Landscapes of COVID-19 and Influenza Patients

Abstract: The coronavirus disease 2019 (COVID-19) pandemic poses a current world-wide public health threat. However, little is known about its hallmarks compared to other infectious diseases. Here, we report the single-cell transcriptional landscape of longitudinally collected peripheral blood mononuclear cells (PBMCs) in both COVID-19- and influenza A virus (IAV)-infected patients. We observed increase of plasma cells in both COVID-19 and IAV patients and XIAP associated factor 1 (XAF1)-, tumor necrosis factor (TNF)-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
313
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(362 citation statements)
references
References 44 publications
30
313
2
Order By: Relevance
“…While we only have samples from the early stage in a severe patient and cannot assess the change in late stage, another study has shown that the cytokines related to IFN-I, such as IFNa, did not decrease in severe condition over time (Lucas et al, 2020). Second, we found different proportions of immune subsets in different conditions that consistent with recent studies (Lee et al, 2020;Liao et al, 2020;Lucas et al, 2020;Wilk et al, 2020;Zhu et al, 2020), including the increased plasma B cells and decreased T subsets in severe conditions. Higher proportions of T subsets were marked in moderate condition, and TCR analysis showed increased clonal expansion of T cells compared to other conditions .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While we only have samples from the early stage in a severe patient and cannot assess the change in late stage, another study has shown that the cytokines related to IFN-I, such as IFNa, did not decrease in severe condition over time (Lucas et al, 2020). Second, we found different proportions of immune subsets in different conditions that consistent with recent studies (Lee et al, 2020;Liao et al, 2020;Lucas et al, 2020;Wilk et al, 2020;Zhu et al, 2020), including the increased plasma B cells and decreased T subsets in severe conditions. Higher proportions of T subsets were marked in moderate condition, and TCR analysis showed increased clonal expansion of T cells compared to other conditions .…”
Section: Discussionsupporting
confidence: 92%
“…However, severe patients have much higher expression of these genes (Figure 5g), indicating more robust activation of IFN-I signaling pathway response and a pro-inflammatory state. Notably, we also found increased expression of STAT1 in severe patients (Figure 5g), which was consistent with a previous study (Zhu et al, 2020).…”
Section: Features Of B Cells and Expansion And Specific Rearrangementsupporting
confidence: 93%
See 1 more Smart Citation
“…Possibly in relation to the overt subset-selective T apoptosis reported for COVID-19 24 , we found signi cantly increased and sustained levels of plasma markers associated with apoptosis. Among these, we observed consistent increases in the levels of CASP8, TNFSF14 and TGFB1, three biomarkers established to be related to in ammation combined with apoptosis.…”
Section: Sustained Markers Related To Apoptosis and In Ammationsupporting
confidence: 56%
“…Interestingly, we found the death and apoptosis process were mainly shown in the biological process panel. A recent report showed that XAF1, TNNF, and FAS induce T cell apoptosis in COVID-19 patients (16). The previous report showed cilium abnormalities in bronchus are associated with COVID-19 (17).…”
Section: Discussionmentioning
confidence: 95%